Infestations Myxobolus sp. in Gills Koi (Cyprinus carpio) That No Clinical Symptoms - Zulkifli; Novia Christi Prihartini (Samakia : Jurnal Ilmu Perikanan, 2020)
Ornamental fish trade between regions in Indonesia allows the transfer of disease, especially if the disease does not show clinical symptoms in fish traded. Koi fish in Tahuna, North Sulawesi, mostly come from the area of ​​East Java, which is one area with many cases of myxobolusis. In addition, the potential for parasitic diseases that come along when koi fish are brought between areas cannot be avoided, because the examination of parasites, especially Myxobolus sp. no longer listed in the regulation as a quarantine inspection requirement. The purpose of this study was to see the Myxobolus sp infestation that infected koi in Tahuna, North Sulawesi, although there were no clinical symptoms using conventional techniques and histopathology. The results of the examination showed Myxobolus spore infestation on the gills of the koi, although the amount was not much, both conventional and histopathological techniques. This shows that our level of awareness of the types of parasites that can infect fish is still lacking. Myxobolus sp is only transmitted through the spore stage back and forth; there is no horizontal or vertical transmission in fish or tubifex T worm populations. More knowledge regarding the life cycle of the Myxobolus sp. in order to obtain the right handling to deal with outbreaks, especially water quality management at the location of the cultivation.